LAMA2‐related myopathy: Frequency among congenital and limb‐girdle muscular dystrophies. Issue 4 (13th August 2015) - Løkken, Nicoline; Born, Alfred Peter; Duno, Morten; Vissing, John
ABSTRACT: Introduction : Muscular dystrophy caused by LAMA2‐ gene mutations is an autosomal recessive disease typically presenting as a severe, early‐onset congenital muscular dystrophy (CMD). However, milder cases with a limb‐girdle type muscular dystrophy (LGMD) have been described. Methods : In this study, we assessed the frequency and phenotypic spectrum of LAMA2 ‐related muscular dystrophy in CMD ( n  = 18) and LGMD2 ( n  = 128) cohorts identified in the last 15 years in eastern Denmark. The medical history, brain‐MRI, muscle pathology, muscle laminin‐α2 expression, and genetic analyses were assessed. Results : Molecular genetics revealed 2 pathogenic LAMA2 mutations in 5 of 18 CMD and 3 of 128 LGMD patients, corresponding to a LAMA2‐ mutation frequency of 28% in the CMD and 2.3% in the LGMD cohorts, respectively. Conclusions : This study demonstrates a wide clinical spectrum of LAMA2 ‐related muscular dystrophy and its prevalence in an LGMD2 cohort, which indicates that LAMA2 muscular dystrophy should be included in the LGMD2 nomenclature. Muscle Nerve 52: 547–553, 2015